2007
DOI: 10.1111/j.1525-1446.2007.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Perspectives on the Rising Incidence of Pertussis

Abstract: Efforts are needed to increase health care providers' knowledge of pertussis disease and vaccines, improve on-time infant immunization rates, promote immunization registries and public health surveillance, and ensure adequate compensation for vaccine purchase and administration. Universal recommendations for and widespread use of acellular pertussis vaccines in adolescents are the most effective measures in controlling the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Pertussis is a problem in developed, urbanized communities and the associated social and health costs are high. 2,28,29 The results of a Spanish study by Fernández-Cano et al 30 found that the economic costs of cases >15 years of age were greater than those of cases <1 year of age, which supports the importance of detecting cases in older children and adolescents as soon as possible to avoid new cases by means of preventive measures such as chemoprophylaxis and vaccination of unimmunized or underimmunized exposed contacts. 14 The role of adults in transmitting B. pertussis to children has been described by several authors.…”
Section: Discussionmentioning
confidence: 89%
“…Pertussis is a problem in developed, urbanized communities and the associated social and health costs are high. 2,28,29 The results of a Spanish study by Fernández-Cano et al 30 found that the economic costs of cases >15 years of age were greater than those of cases <1 year of age, which supports the importance of detecting cases in older children and adolescents as soon as possible to avoid new cases by means of preventive measures such as chemoprophylaxis and vaccination of unimmunized or underimmunized exposed contacts. 14 The role of adults in transmitting B. pertussis to children has been described by several authors.…”
Section: Discussionmentioning
confidence: 89%
“…Usually clinicians associate pertussis with children and lack of knowledge or appreciation of clinical illness caused by pertussis in adults often renders it unrecognized. Undiagnosed cases contributed to the spread of pertussis to others who are susceptible (e.g., incompletely immunized infants and toddlers) [33]. The General Practitioners must be encouraged in considering the diagnosis of pertussis as part of differential diagnosis of each adult with a prolonged cough.…”
Section: Discussionmentioning
confidence: 99%
“…17 Furthermore, pertussis often causes other complications for adults and adolescents, such as missing several days of work and school and public health surveillance costs. [18][19][20] In the U.S., adolescent and adult family members are also often the source of pertussis exposure in young infants, who are at greatest risk for health complications resulting from the disease including pneumonia, convulsions, apnea, and death. 17 Infants must build immunity to pertussis through a series of vaccinations.…”
Section: Vaccination Recommendations and Ratesmentioning
confidence: 99%